Successful management of tracheal lobular capillary hemangioma with arterial embolization followed by electrosurgical snaring via flexible bronchoscopy in an 11-year-old boy: A case report and literature review - Tao, Xiaofen; Wu, Lei; Li, Shuxian; Wu, Yuxin; Lai, Can; Chen, Enguo; Chen, Zhenjie; Jin, Guoping; Wang, Yingshuo (Frontiers in Medicine, 2023)
Lobular capillary hemangioma (LCH), previously known as pyogenic granuloma, is a benign vascular lesion commonly found within the oral and nasal cavities. However, it is rarely encountered within the trachea, especially in pediatric patients, where it manifests as hemoptysis, cough, and wheeze, and is frequently misdiagnosed as bronchitis or asthma. There is limited literature on the presentation, behavior, and management of tracheal LCH. Herein, we describe a rare case of tracheal LCH in an 11-year-old boy with a history of hemoptysis, which was successfully managed with arterial embolization followed by electrocautery loop snaring via flexible bronchoscopy. No complications occurred during and after the procedure. A review of the relevant literature is also provided. Our case is unique, given the therapeutic strategy utilized for pediatric tracheal LCH, and reminds physicians to be aware of tracheal LCH in the differential diagnosis for hemoptysis.